2022
DOI: 10.1002/hbm.25796
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in EEG band power at subject‐specific timescales over minutes to days explain changes in seizure evolutions

Abstract: Epilepsy is recognised as a dynamic disease, where both seizure susceptibility and seizure characteristics themselves change over time. Specifically, we recently quantified the variable electrographic spatio‐temporal seizure evolutions that exist within individual patients. This variability appears to follow subject‐specific circadian, or longer, timescale modulations. It is therefore important to know whether continuously recorded interictaliEEG features can capture signatures of these modulations over differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 91 publications
1
15
0
Order By: Relevance
“… 17 , 46 However, the factors that modulate seizure durations within the same patient are unknown. We previously hypothesized that preictal variability in brain dynamics 4 or continuous fluctuations in interictal brain dynamics 47 could produce changes in seizure pathways. Likewise, fluctuations in interictal markers 48 such as levels of cortical excitability and inhibition, 49–51 interictal spike rate, 52 , 53 or functional networks 54 could potentially affect seizure duration.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 46 However, the factors that modulate seizure durations within the same patient are unknown. We previously hypothesized that preictal variability in brain dynamics 4 or continuous fluctuations in interictal brain dynamics 47 could produce changes in seizure pathways. Likewise, fluctuations in interictal markers 48 such as levels of cortical excitability and inhibition, 49–51 interictal spike rate, 52 , 53 or functional networks 54 could potentially affect seizure duration.…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical seizures are also reported to follow a circadian pattern 15 . Recent studies also reported modulations at circadian and longer timescales within many patients in terms of seizure electrographic evolutions 38,39 and other seizure properties 40 . In agreement with previous literature, we found evidence that EEG‐based seizure severity markers are modulated on circadian and longer timescales, although the effect size of the modulation is patient‐specific and weak in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Second, as with seizure occurrence Leguia et al, 2021;Maturana et al, 2020), different cycles likely interact to produce the observed seizure variability. A predictive model incorporating multiple timescales may be more informative than a single spike rate cycle (Panagiotopoulou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, variability in seizure onset and spread have been linked to preictal and interictal changes in network features (Khambhati et al, 2016), band power (Naftulin et al, 2018), the location of high frequency oscillations (Gliske et al, 2018), and patterns of cortical excitability (Badawy et al, 2009). The same interictal features (network dynamics (Kuhnert et al, 2010;Mitsis et al, 2020), band power (Panagiotopoulou et al, 2021), high frequency activity (Chen et al, 2021), and cortical excitability (Meisel et al, 2015)) have all been shown to vary over circadian and/or multidien cycles. We now show that seizure evolutions also change over the timescales that influence interictal brain dynamics, suggesting that these fluctuations share common mechanisms.…”
Section: Discussionmentioning
confidence: 99%